Distributed wikis: a survey. (28th November 2014) - Davoust, Alan; Skaf‐Molli, Hala; Molli, Pascal; Esfandiari, Babak; Aslan, Khaled; Smari, Waleed W.; Navarro, Antonio M.; McQuay, William K.
Summary 'Distributed wiki' is a generic term covering various systems, including 'peer‐to‐peer wiki', 'mobile wiki', 'offline wiki', 'federated wiki' and others. Distributed wikis distribute their pages among the sites of autonomous participants to address various motivations, including high availability of data, new collaboration models and different viewpoints of subjects. Although existing systems share some common basic concepts, it is often difficult to understand the specificity of each one, the underlying complexities or the best context in which to use it. In this paper, we define, classify and characterize distributed wikis. We identify three classes of distributed wiki systems, each using a different collaboration model and distribution scheme for its pages: highly available wikis, decentralized social wikis and federated wikis. We classify existing distributed wikis according to these classes. We detail their underlying complexities and social and technical motivations. We also highlight some directions for research and opportunities for new systems with original social and technical motivations. Copyright © 2014 John Wiley & Sons, Ltd.